2009
DOI: 10.1130/b26459.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the probability and volume of postwildfire debris flows in the intermountain western United States

Abstract: Empirical models to estimate the probability of occurrence and volume of postwildfi re debris fl ows can be quickly implemented in a geographic information system (GIS) to generate debris-fl ow hazard maps either before or immediately following wildfi res. Models that can be used to calculate the probability of debris-fl ow production from individual drainage basins in response to a given storm were developed using logistic regression analyses of a database from 388 basins located in 15 burned areas located th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
242
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 238 publications
(271 citation statements)
references
References 35 publications
4
242
0
5
Order By: Relevance
“…Complete model output for each of the basins examined in this study can be found in Appendix A. States: Arizona (Wohl and Pearthree, 1991), California (Doehring, 1968), Colorado (Cannon et al, 1998), Idaho (Cannon et al, 2010;Meyer et al, 2001) and Utah (Giraud and McDonald, 2007;, as shown in Figure 6a. Measured volumes of these debris flows range from 1700 m 3 to around 100,000 m 3 , and the proportion of the basins burned at moderate and high severity ranged from 0.3469 to 0.…”
Section: Example Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Complete model output for each of the basins examined in this study can be found in Appendix A. States: Arizona (Wohl and Pearthree, 1991), California (Doehring, 1968), Colorado (Cannon et al, 1998), Idaho (Cannon et al, 2010;Meyer et al, 2001) and Utah (Giraud and McDonald, 2007;, as shown in Figure 6a. Measured volumes of these debris flows range from 1700 m 3 to around 100,000 m 3 , and the proportion of the basins burned at moderate and high severity ranged from 0.3469 to 0.…”
Section: Example Resultsmentioning
confidence: 99%
“…Cannon et al (2010) compiled a list of the most common of these variables and assessed their impact on the debris flows in the same database that is used in this study. These variables describe a range of factors, including basin morphology, basin areas burned at different severities, soil material properties, rock type, and rainfall amounts and intensities.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations